GURU SEBAGAI AGEN MORAL: MENANGKAL HEDONISME DALAM DUNIA PENDIDIKAN - Wulandari, Yuni; Nirwana, Padma; Yasir, Muhammad; Insani, Rahmah; Maulana, Sasmita; Bintang, Hikmal; Iryani, Eva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growing prevalence of hedonism among students poses a serious challenge in the world of education, as it can influence students’ attitudes, behaviors, and motivation to learn. This study aims to examine the role of teachers as moral agents in countering the influence of hedonism in the educational environment. This study employs a qualitative approach in the form of a literature review, utilizing secondary data obtained from scientific journals, books, and relevant articles. Data collection was conducted through a literature review by tracing and analyzing various sources, while data analysis employed qualitative descriptive techniques through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that hedonism among students is influenced by technological advancements, social media, and social environments that encourage consumerist behavior and an orientation toward instant gratification. In this context, teachers play a crucial role as moral agents through setting a good example, reinforcing character education, and guiding the wise use of technology. The role of teachers is highly strategic in shaping students’ character and countering the influence of hedonism by consistently instilling the values of discipline, responsibility, and simplicity.